(untitled) (Journal of EAHIL, 2017)
The 14th EAHIL Conference in Rome was a great success in all aspects, scientific and social and our last issue’s content is witness to this. The reports of the Rome Conference Continuing Education Courses are presented in this issue and make very interesting reading. Also we have information regarding the EAHIL workshop in Edinburgh in June 2015 which I am sure everyone will be pleased to have. At the same the new EAHIL Scholarship Award Scheme procedure for 2015 with a revised eligibility and evaluation criteria devised by the EAHIL Executive Board will be announced.